Issues on construction waste: the need for sustainable waste management - Nagapan, Sasitharan (2012)
Construction wastes have become a pressing issue in many developing countries and have adverse effects on environment, economy and social aspects. Illegal dumping is a common issue created from the physical construction waste and besides that non physical waste like cost and time overruns are not properly addressed among the construction players. This paper explores the impacts of construction on sustainable construction and contributing causes which will help the practitioners to formulate ways in avoiding or reducing the waste. It also highlights the sustainable approach in managing the construction waste as practice.